Cambridge proficiency examination practice 1 - by Leo Jones (Cambridge University Press, 1984)
Cambridge Proficiency Examination Practice 1 contains five complete sets of authentic past papers from the University of Cambridge Local Examinations Syndicate issued in recent years for the Cambridge Proficiency Examination. The practice tests are reproduced in exactly the same form as in the examination itself. The accompanying cassettes contain the recorded material and instructions for the listening comprehension questions, which are also presented in the same form that students will meet in the examination. The accompanying Teacher's Book contains a full introduction to the exam, including notes on CPE examiners' marking criteria - especially in relation to the Writing paper - plus the tapescript and keys to each test